USM RECEIVES A 15-MEMBER DELEGATION FROM A JOU UNIVERSITY KOREA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 18 August 2016 – Universiti Sains Malaysia (USM) recently received a 15member delegation from Ajou University Korea, on a visit to Penang to gather first hand information on USM particularly concerning USM’s longstanding involvement in the area of lifelong learning.